Religiosity: Conflict Resolution in the Hikayat Prang Cumbok - Rusli, Herman; Mukhlis, Mukhlis (Jurnal Ilmiah Peuradeun, 2023)
This study interpreted the religiosity aspect of the Hikayat Prang Cumbok as a method of resolving social and ethnic conflicts in Aceh. What were the problems explored by the value of religiosity that caused the emergence of social conflicts in Aceh, and what concepts of religiosity were the alternative resolutions for resolving these social conflicts? The data collection method used was the manuscript study method. The data was taken from the text of the Hikayat Prang Cumbok because this saga is powerful in telling the reality of social conflict in Aceh. The data were analyzed in descriptive qualitative. The results of the study showed that the aspect of religiosity that appears in the Hikayat Prang Cumbok can be seen in three forms: (1) social religiosity, (2) divine religiosity, and (3) universal religiosity. The religiosity aspect of conflict resolution in this saga is based on reasons of faith and morality. Aqeedah is related to the relationship with Allah (hambluminallah), while morality is related to the relationship between humans (hambluminannas) and humans and the universe. From these three things, it can be seen that morality towards humans and the universe cannot be separated from morality towards God.